2022
DOI: 10.1158/2159-8290.cd-21-1593
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant PD-1 Blockade in Resected Melanoma: Is Preventing Recurrence Enough?

Abstract: Summary: Grossmann and colleagues report the results of a large randomized trial demonstrating improved recurrence-free survival with adjuvant pembrolizumab in resected melanoma compared with adjuvant ipilimumab or IFNα2b. However, it remains unclear whether adjuvant immunotherapies extend overall survival as outcomes for patients with advanced melanoma continue to improve. See related article by Grossmann et al., p. 644 (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In other recent trials evaluating adjuvant PD-1 antibodies (eg, CheckMate 238, SWOG S1404, and KEYNOTE-054), the lack of OS benefit despite RFS benefit raises questions of whether waiting for recurrence and receiving treatment for metastatic disease would be acceptable to patients. 5,[22][23][24] This is complicated by the active control arms in the two trials (CheckMate 238 and SWOG S1404) that have reported OS data thus far and the relative immaturity of those OS data. 5,22 Longer follow-up is needed for these trials to ascertain any long-term benefits with adjuvant PD-1 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…In other recent trials evaluating adjuvant PD-1 antibodies (eg, CheckMate 238, SWOG S1404, and KEYNOTE-054), the lack of OS benefit despite RFS benefit raises questions of whether waiting for recurrence and receiving treatment for metastatic disease would be acceptable to patients. 5,[22][23][24] This is complicated by the active control arms in the two trials (CheckMate 238 and SWOG S1404) that have reported OS data thus far and the relative immaturity of those OS data. 5,22 Longer follow-up is needed for these trials to ascertain any long-term benefits with adjuvant PD-1 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a question of whether waiting for recurrence and receiving treatment for metastatic disease might be acceptable to patients was raised, and this may help avoid the risk of potentially irreversible immune-related adverse events in patients whose disease can be cured with surgery alone. 53 , 54 The oncologists need to discuss the known DFS benefits and the lack of OS benefit and side effects in the relatively short follow-up to date with the patient before making an adjuvant therapy decision. And assays like circulating tumor DNA (ctDNA), circulating tumor cells, tumor mutation burden (TMB), or exosome vesicles might be helpful in determining which patients are at a higher risk of disease recurrence after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to 2015, interferon-α 2b was the only approved agent for adjuvant treatment of patients with high-risk cutaneous melanoma [ 115 , 116 , 117 , 118 ]. Interferon-α-2b exhibits anti-tumour activity by enhancing natural-killer cell activity as well as tumour antigen presentation and has been shown to have anti-proliferation and anti-angiogenic effects [ 115 ].…”
Section: The Era Of Immunotherapymentioning
confidence: 99%